Analisis Yuridis Dakwaan Jaksa Penuntut Umum Dalam Tindak Pidana Kekerasan Fisik Dalam Rumah Tangga Terhadap Korban Anak Tiri - Gundred, Bob; Tanuwijaya, Fanny; Prihatmini, Sapti (Pusat Studi Gender Universitas Jember, 2025)
The aim of this thesis research is to analyze the application of suitability between the indictment and subsidiary form made by the Public Prosecutor with the articles in which they are accused, and to analyze the suitability of the description evidence of information witnesses with documentary evidence in the form of Visum et Repertum according to Article 184 Paragraph (1) of the Criminal Procedure Code. The study of the problem formulation and the conclusions are stated based on the author's arguments which were formulated using a deductive method, namely a method that relies on basic principles leading to special principles. The indictment in the form of a subsidiary in Verdict Number 301/Pid.Sus/2019/PN Tte is in accordance with the articles charged, however the indictment in the form of a subsidiary as a prosecution strategy is not in accordance with the procedure for making an indictment which should be in the form of alternative, because the use of each the law is exclusionary at other levels. The evidentiary system according to Article 184 of the Criminal Procedure Code, Visum et Repertum and witness statements remain valid evidence as long as there is no other evidence that disputes their truth. Although there is a discrepancy between the witnesses’ statements and the Visum et Repertum, due to the possibility of quite a large time difference between the criminal incident and the Visum examination, this could result in an examination for bleeding in the ear not being carried out because the wound had dried up.